The book of heroines : tales of history's gutsiest gals - Drimmer, Stephanie Warren (Washington, D.C National GeographicPartners, 2016)
"Everybody needs a role model! Discover true stories of superstars, war heroes, world leaders, gusty gals, and everyday women who changed the world. From Sacagawea to Mother Teresa, Annie Oakley to Malala Yousafzai, these famous women hiked up their pants and petticoats and charged full-speed ahead to prove girls are just as tough as boys...maybe even tougher. Complete with amazing images and a fun design, this is the book that every kid with a goal, hope, or dream will want to own"--
Includes index.
Keywords: Women heroes -- Biography -- Juvenile literature; Women -- Biography -- Juvenile literature; Courage -- History -- Anecdotes -- Juvenile literature; World history -- Anecdotes -- Juvenile literature; JUVENILE NONFICTION / Girls & Women